Unilateral Straight Hair-A Symptom of Acquired Horner's Syndrome in a Neonate - Chantal Ott; Andrei Bobylev; Stefan Gerhard Holland-Cunz; Johannes Mayr (Georg Thieme Verlag KG, 2018)
A multicystic tumor of the right neck was detected in a girl at 29 weeks of gestation by fetal ultrasound and magnetic resonance imaging (MRI). The baby was delivered by cesarean section at week 37 of gestation. The newborn adapted well, with minimal compromise of breathing and drinking. Postnatal ultrasound and MRI revealed a cervical lymphangioma measuring 60.5 × 60.6 × 41.2 mm. We performed subtotal resection of the tumor when the girl was 34 days. As a complication of surgical resection, the girl developed ipsilateral Horner's syndrome. In the postoperative period, her curled hair turned straight at the side of the head affected by Horner's syndrome. At the age of 2.5 years, ultrasonic imaging revealed the presence of three cysts measuring 3 mm in diameter each. Horner's syndrome had improved, and the texture of the girl's hair had become curly again on both sides.